Unveiling The Discourse of Fraud in The United States Presidential Election 2020 with Normal Fairclough Critical Discourse Analysis - Nasirudin, Didin (Syntax Corporation, 2024)
The political rise of Donald Trump in the United States was unprecedented, characterized by his deviation from traditional political norms and his use of divisive rhetoric against minorities, Muslims, China, and immigrants. Trump's strategy of galvanizing conservative white Evangelicals led to his unexpected victory in the 2016 presidential election. During his 2020 reelection campaign, Trump employed similar tactics; however, his handling of the COVID-19 pandemic and the resulting economic downturn eroded his support compared to his Democratic rival, Joe Biden. Anticipating electoral defeat, Trump preemptively alleged widespread electoral fraud, specifically targeting mail-in voting policies. After losing the election, with an electoral count of 232 to Biden's 306, Trump continued to claim the election was